When Health Care Insurance does not make a Difference – The Case of Health Care `Made in China' - Hendrik P. van Dalen (Tinbergen Institute, 2006)
Does medical insurance affect health care demand and in the end contribute to improvements in the health status? Evidence for China for the year 2004, by means of the China Health and Nutrition Survey (CHNS), shows that health insurance does not affect health care demand in a significant manner. Counterfactuals suggest that full insurance coverage of the Chinese population will not radically change the health care decisions and may even enlarge the perverse effects of today's health care system: insured persons are more likely to fall back on self-care when they are injured or ill than on the care of a local clinic. This effect is particularly strong in urban areas. In case of a severe injury hospital consultation is preferred to local clinic or self-care by most people, but still a substantial percentage (20 percent) resorts to self-care or ignores the illness. The high level of out-of-pocket expenses paid by both insured and uninsured patients lies at the root of this problem. Insurance does not offer real protection against unpredictable high health care expenditures and can lead people into a position of long-term poverty or serious liquidity problems.
Keywords: D12; H51; I11; I18; P36; 330; health insurance; poverty; China; health care; market failure; Krankenversicherung; Gesundheitsversorgung; Marktversagen; Armut; China